2016
DOI: 10.2298/tsci150831173l
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CO2 concentration on indoor air quality and correlation with relative humidity and indoor air temperature in school buildings in Serbia

Abstract: Previous studies have shown that poorly ventilated classrooms can have negative impact on the health of children and school staff. In most cases, schools in Serbia are ventilated naturally. Considering their high occupancy, classroom air quality test determines the level of air pollution, after which it is possible to implement corrective measures. The research presented in this study was conducted in four schools which are located in different areas and have different architecture designs. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
5
24
0
2
Order By: Relevance
“…The present results are consistent with those of Al-Rashidi et al (2012) and Al-Hubail and Al-Temeemi (2015) regarding CO 2 levels, although in the present work, various hot spots in each school were identified for remediation purposes. CO 2 levels in schools are in concordance with Lazovic et al (2016) for heating season (winter) during low-ventilation practice. The maximum allowed concentration expressed as an 8-hr weighted average during occupational exposure is 5000 ppm (National Institute for Occupational Safety and Health [NIOSH], 2007).…”
Section: Co 2 Data Interpretationsupporting
confidence: 63%
See 1 more Smart Citation
“…The present results are consistent with those of Al-Rashidi et al (2012) and Al-Hubail and Al-Temeemi (2015) regarding CO 2 levels, although in the present work, various hot spots in each school were identified for remediation purposes. CO 2 levels in schools are in concordance with Lazovic et al (2016) for heating season (winter) during low-ventilation practice. The maximum allowed concentration expressed as an 8-hr weighted average during occupational exposure is 5000 ppm (National Institute for Occupational Safety and Health [NIOSH], 2007).…”
Section: Co 2 Data Interpretationsupporting
confidence: 63%
“…Cornaro et al (2011) have discussed indoor CO 2 levels as a measure of effectiveness natural trickle ventilation in middle school in Italy and concluded that further assistance was required to achieve adequate air quality for the occupants. Lazovic et al (2016) have reported impact of CO 2 concentration on IAQ and correlation with temperature and relative humidity in schools in Serbia. Their results showed variability of CO 2 levels as indicative of different ventilation rate for heating season (winter) and nonheating seasons (spring).…”
Section: Introductionmentioning
confidence: 99%
“…Li, et al. analyzed the concentration of CO 2 in different altitudes in the atmosphere [15] . To do this, the authors attached a CO 2 sensor on an air balloon.…”
Section: Experimental System Design and Prediction Methodsmentioning
confidence: 99%
“…Children's respiratory and immune systems are weaker than adult which made them more sensitive to environmental exposure (Oliveira, Slezakova, Delerue-Matos, Pereira, & Morais, 2016). There are several sources that influence the CO₂ concentration such as equipment of ventilation, furniture, human factors (breathing) and activities ( number of pupils in the classroom, class duration, break time) (Lazovic, Stevanovic, & Zivkovic, 2015). Nevertheless, when the classroom experiences full occupancy, the carbon dioxide concentration often exceeds 1500 ppm (Cichowicz et al, 2015).…”
Section: Problem Statementmentioning
confidence: 99%
“…However, it is known that the indoor CO₂ concentration level should not exceeds 1000 ppm as compliance with ASHRAE and ICOP (ICOP, 2010;Salleh, Kamaruzzaman, Riley, Zawawi, & Sulaiman, 2015). Lazovic, Stevanovic, and Zivkovic, (2015) mentioned that the CO₂ concentration acts as an indicator in IAQ. Besides, the CO₂ concentration distribution is affected by the type of ventilation strategy (Mahyuddin & Awbi, 2012).…”
Section: Introductionmentioning
confidence: 99%